PERLINDUNGAN HUKUM BAGI ANAK KORBAN KEKERASAN SEKSUAL YANG DILAKUKAN ORANG TUANYA - Joko Susanto (Qistie Jurnal Ilmu Hukum, 2020)
Along with the development of technology and human civilization, crimes that occur are not only related to crimes against life and property, but crimes against decency are also increasing. As a social problem, the crime of sexual violence up to now has been carried out by many Indonesian people both by adults and elderly, even fathers to their own children and most of the victims are women and children. Sexual violence is violence that occurs because of the problem of sexuality. The purpose of this journal is to find out how the legal protection for child victims of sexual violence by their own parents. The discussion method used is the normative legal method, namely the statutory approach (The Statute Approach). Sexual violence is generally done against a partner. This violence includes all types of sexual violence committed against a sexual partner. Including sexual violence is violence committed by a husband against his wife, solely because they want to satisfy their biological desires. The crime of rape is very worrying especially if the victim is a child who is still under age, because this will affect the psychological development of children, cause lifelong trauma and more sadly the child victims of rape can become prostitution workers.